Efeito do sexo, faixa etária e poder econômico na preferência por idade de parceiros - Silva Filho, José Eduardo da (2023)
Age is important in choosing a mating partner, as it is associated with many attributes that contribute to an individual's mating value. This study investigated how sex, age, and economic power can influence patterns of age preference for an idealized partner and partner choice. Heterosexual individuals of both sexes participated in the study, ranging in age from 12 to 32 years and belonging to various economic power classes. This research presents a quasi-experimental design with a sample of 2504 participants (1560 women) for preference analysis and a sub-sample of 1443 participants (931 women) for choice analysis. All participants completed questionnaires providing sociodemographic data, indicating the minimum, maximum, and ideal age for an idealized partner, and responded to an instrument that assessed their economic power. Those involved in romantic relationships also indicated their partners' ages. General linear models were applied to investigate the effect of sex (female and male), age range (12-17 years | Adolescents, 18- 23 years | Young Adults, and 24-32 years | Adults), and economic power (A-B1 | High, B2-C1 | Intermediate, and C2-DE | Low) on the difference between the indicated ages and the participants' ages. In general, it was observed that men prefer partners with younger minimum, maximum, and ideal ages when compared to women. Men prefer increasingly younger partners (minimum and ideal age) as their age increases, and adolescent males idealize partners older than themselves. Women prefer partners older than themselves (3.41 years) and with a minimum age close to their own, but adult women accept younger partners (minimum and maximum age). Preferences were manifested in choices, as women have older partners when compared to men. Economic power influenced both preferences and choices. Adult women with lower economic power accept partners with a younger minimum age, while adult men with lower economic power accept partners with a higher minimum age, a finding that may represent a reduction in the level of demand due to lower mating value originating from low economic power. It was also found that adolescents with higher economic power seek partners with a higher maximum age, indicating that having high economic power would make adolescents more demanding in seeking partners. Finally, the effect of economic power on choices was observed, as adult women with lower economic power formed pairs with younger men. It was concluded that sex, age, and economic power influence preferences and choices and that economic power can influence mating value by affecting demand levels in seeking partners. These findings expand the understanding of the importance of socioeconomic status in relationships.